Network Monitoring Measurements for Quality of Service: A Review - Alkenani, Jawad; Nassar, Khulood Ahmed (Iraqi Journal for Electrical and Electronic Engineering, 2022)
One crucial challenge confronting operators worldwide is how to ensure that everything runs smoothly as well as how to monitor the network. The monitoring system should be accurate, easy to use, and quick enough to reflect network performance in a timely way. Passive network monitoring is an excellent tool for this. It could be used to look for issues with a single network device or a large-scale issue affecting the whole LAN or core network. However, passive network monitoring is not limited to issue resolution; it could also be used to generate network statistics and measure network performance. As shown in this review, it is a very strong tool, as seen by the sheer volume of data published on Google Scholar. The main objective of this review is to analyze and comprehend monitoring measurements for quality of service to serve as a resource for future research and application. Essential terms and concepts of network monitoring and their quality of service are presented. Network monitoring measurements (which can be passive, active, or hybrid) and their wireless network monitoring tools (which can be public domain or commercial tools) are also covered in terms of relevance, advantages, and disadvantages. Finally, the review is summarized.